Integration of Mapbox and Google Maps to Support Additional Features in Geographic Information Systems - Hidayatulloh, Rahmad; Airlangga, Primaadi (SAINTEKBU, 2022)
AnÂ integrated geographic information systemÂ is a geographic information system that aims to facilitate the creation and integration of mapping data so that researchers from various backgrounds can present their research results in the form of a map and can be combined on a larger scale. In making an integrated geographic information system, the use of the maps box was chosen because the maps box is a tool for making mapping that is free of charge both in making mappings and displaying mapping results so; it can save costs because the number of accessors and mappings made will incur substantial costs if using a paid alternative. However, the Maps box has many shortcomings in terms of features, so we researched to integrate third-party applications to fulfill the features that need to be added in the maps box. To overcome the shortcomings of the map box, the researcher integrates the route feature of Google Maps, integrates the location details feature on Google Maps, and integrates Google Maps coordinate data via the Google Maps link, which can be stored in the system so that these features can be used in an integrated geographic information system. Integrating third-party applications can create an integrated geographic information system using a map box but can also have more features.